EFEKTIFITAS SISTEM PENGELOLAAN KEUANGAN DAN ASET DAERAH: (Studi kasus BPK dan Aset Daerah, Kabupaten Lamongan) - Laily Chodariyanti (STIE Mahardhika, 2019)
Financial and asset management area must be transparent and accountable in accordance with the principle of good governance. However, in Lamongan financial and asset management area is not running optimally. This research was conducted to describe and analyze the financial and asset management area processes as well as problems in the area of financial and asset management in Lamongan. This research used a descriptive method qualitative approach and using an interactive model of data analysis from Miles Huberman. Research results showed the financial and assets management area in Lamongan is not optimal. There are still obstacles in management, there are constraints on the discussion of budget planning areas that are not timely in the legislature and the lack of human resources accounting background. In the asset management area there are problems in the areas of asset inventory data processing is still less well and local government land that has not been certified.